Youth, Da'wah, and Nationalism: The Perspective of Idhatun Nasyi'in by Mushtofa Al-Ghalayain and Its Relevance to the Socio-Cultural Context of the Indonesian Nation - Mustakharoh, Fajriatul; Khotimah, Khusnul; Ala, Chisnul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Youth hold a central role in the advancement of civilization, yet they are highly susceptible to external influences, including moral decline and ideological threats. One of the pressing issues is the rise of transnational movements that diminish the value of nationalism, often portraying it as incompatible with religious belief. This article explores Mushtofa Al-Ghalayain’s thoughts on youth, Islamic preaching (da’wah), and nationalism as articulated in his work Idhatun Nasyi’in. Al-Ghalayain highlights wathaniyah (nationalism) as an essential quality for youth, asserting that love and service to the homeland are integral to faith. He positions youth as the main drivers of societal transformation and upholders of national dignity. The research employs a qualitative content analysis approach to examine how the text conveys moral, religious, and nationalistic values. Findings suggest that religion and nationalism are not opposing forces but are mutually reinforcing in shaping responsible, morally grounded citizens. Da’wah, therefore, must contribute not only to spiritual growth but also to the unity and integrity of the nation. This vision is reflected in the well-known maxim: